Menakar Implementasi Kebijakan Keselamatan dan Kesehatan Kerja di Indonesia - Masrully Masrully (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2019)
The number of work accidents, especially in government projects at the end of 2017 until the beginning of 2018, indicates that the occupational safety and health (OSH) is still a issue that needs to be studied its implementation in Indonesia. BPJS Employment data shows that the number of work accidents in Indonesia over the past 3 years is indeed fluctuative, but still quite high. These facts and data make the issue of OSH important to be reviewed in its implementation. Because the issue of OSH has actually been regulated by the government through Undang-Undang No. 1 of 1970 concerning Occupational Safety. This policy has been implemented for almost half a century. For this reason, the paper tries to review the performance of OSH policy implementation in Indonesia. The method used is desk research. The performance of OSH policy implementation was measured using the policy implementation theory proposed by Ripley and Franklin. Data is collected by literature study methods from report documents, websites, mass media, and official publications issued by authorized institutions. The research also analyzes the factors that cause high work accidents in Indonesia and formulates strategies to solve them. The study concluded that the performance of OSH policy implementation was still low. This can be seen from the low compliance of the target group and the realization of policy objectives. Factors that cause the low performance of policy implementation are due to weak regulation, weak supervision, low level of compliance, weak commitment, and incorrect mindset about K3. For this reason, research recommends improving the K3 Act, increasing the number of labor inspectors, and implementing programs. improve public mindset, especially target groups about K3.Â